2017
DOI: 10.1007/s13300-017-0334-8
|View full text |Cite
|
Sign up to set email alerts
|

A 32-Week Randomized Comparison of Stepwise Insulin Intensification of Biphasic Insulin Aspart (BIAsp 30) Versus Basal–Bolus Therapy in Insulin-Naïve Patients with Type 2 Diabetes

Abstract: IntroductionThis 32-week, open-label, randomized, parallel-group, multinational trial aimed to compare the efficacy and safety of stepwise insulin intensification of biphasic insulin aspart 30 (BIAsp 30) relative to stepwise intensification of a basal–bolus regimen in insulin-naïve adults with type 2 diabetes (T2D) who continued pretrial treatment with metformin and sulfonylurea.MethodsAdults with T2D were randomized into one of two treatment arms for 32 weeks: (1) BIAsp 30 once daily (OD), with the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A total of 9691 patients were included in the analysis. The most common BA insulin treatments were insulin glargine 100 U/mL (19 studies: [ 2 , 13 – 15 , 17 24 , 26 32 ]) and insulin aspart (11 studies: [ 15 , 16 , 18 20 , 22 , 23 , 25 , 31 33 ]). The patient characteristics in each trial are also reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 9691 patients were included in the analysis. The most common BA insulin treatments were insulin glargine 100 U/mL (19 studies: [ 2 , 13 – 15 , 17 24 , 26 32 ]) and insulin aspart (11 studies: [ 15 , 16 , 18 20 , 22 , 23 , 25 , 31 33 ]). The patient characteristics in each trial are also reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…There was generally a low risk of selection bias across the studies, with some studies judged as having an unclear risk of such bias. In eight studies [ 13 , 16 , 18 , 20 , 25 , 28 , 32 , 33 ], inadequate methods of generating the randomization sequence were reported; similarly, seven studies were judged to have an unclear risk of allocation concealment due to insufficient details [ 2 , 13 , 15 , 16 , 28 , 32 , 33 ]. Risk of performance bias (pertaining to the blinding of participants and personnel) and risk of detection bias (pertaining to blinding of outcome assessment) were primarily judged to be high, as most of the studies had an open-label study design.…”
Section: Resultsmentioning
confidence: 99%
“…The comprehensive review by Krishnasamy and Abell describes diabetic gastroparesis in detail [ 6 ]. Defined as delayed gastric emptying with associated upper gastrointestinal symptoms in the absence of any mechanical obstruction [ 7 ], diabetic gastroparesis may present with a variety of symptoms.…”
Section: Diabetic Gastroparesismentioning
confidence: 99%
“…The long list of complaints is accompanied by an equally exhaustive list of differential diagnoses, including iatrogenic or drug-induced delay in gastric emptying. Diabetic gastroparesis is accoutered by poor glucose control, suboptimal nutritional and hydration status, greater risk of CVD, hypertension and retinopathy, frequent need for hospitalization, and poor quality of life [ 6 ]. Thus, diabetic gastroparesis is not only a marker of poor current control but also a predictor of poor future outcomes.…”
Section: Diabetic Gastroparesismentioning
confidence: 99%
See 1 more Smart Citation